Census Estimates of Algal and Epiphytic Carbonate Production Highlight Tropical Seagrass Meadows as Sediment Production Hotspots - Perry, Chris T.; Salter, Michael A.; Morgan, Kyle M.; Harborne, Alastair R. (Frontiers in Marine Science, 2019)
Tropical shelf, platform and reef-lagoon systems are dominated by calcium carbonate (CaCO3) sediments. Data on habitat-specific CaCO3 production rates are however sparse, limiting understanding of where and in what form CaCO3 sediment is produced, and how habitat type and scale influence shallow marine sediment production budgets. Using novel census methodologies, based primarily on measures of plant biovolumes and carbonate content, we assessed habitat-scale production by two ubiquitous biogenic CaCO3 producers, calcareous green algae and seagrass epiphytes, across southern Eleuthera Bank, Bahamas (area ~140 km2). Data from species-specific plant disaggregation experiments and from X-ray diffraction (XRD) analysis of calcified plants also allowed us to resolve questions about the size fractions and mineralogies of the carbonates produced. Production rates varied significantly between habitats (range: 1.8–237.3 g CaCO3 m-2 yr-1), collectively totalling ~0.9 M Kg annually across the study area. Outputs comprise similar amounts of aragonite and high Mg-calcite, and with ~55% of the CaCO3 produced being contributed as mud-grade (<63 μm) sediment. Our analysis also reveals that habitat type and extent - especially of medium and high density seagrass beds - strongly influences the amounts and types of carbonate generated. Indeed, dense seagrass beds were identified as the dominant per unit area production sites, contributing ~18% of total CaCO3 despite covering only 0.5% of the study area. These findings have direct relevance for quantifying present-day sediment budgets and for predicting sediment system-scale responses to changes in habitat extent and productivity.